A IMPORTÂNCIA DO CONHECIMENTO TÁCITO NA FORMAÇÃO DO EDUCADOR - Sugui, Khalil Salem (2008)
This thesis intend to show the importance of the tacit knowledge in the educator formation. Firstly, we intend to explain the main p rts of the tacit knowledge, developed by Michael Polanyi during the XX century. After, we will make an aproximation between the tacit knowledge and the educational space, searching understand the discovery and the human perception, points considered by Polanyi like essentials to constitute our tacit knowledge. Watching the educational space, we will analise, specifically, the teachers of Literature. This dissertation, a bibliographic work, uses theoricals support like Polanyi, and another educational theoricals of Literature teaching, like Claudio Saiani and Antonio Candido.(AU)